Exploring the Impact of Parental Involvement on Academic Motivation among High School Students - Sasa astrina (Mauve Journal De Leardu, 2024)
This observe investigates the impact of parental involvement on excessive faculty college students' academic motivation, that specialize in intrinsic and extrinsic motivational elements. A quantitative technique changed into hired, making use of stratified random sampling to accumulate information from 300 high school students across grades 9-12. Measures blanketed standardized scales for parental involvement and educational motivation, established thru expert evaluation and confirmatory aspect analysis. Statistical analyses, such as Pearson correlation, ANCOVA, and regression, were carried out to have a look at relationships and predictors of motivation, controlling for socioeconomic status and demographic variables. Results suggest great effective correlations among parental involvement and each intrinsic (r = 0.45, p < 0.001) and extrinsic (r = 0.32, p = 0.003) motivation. ANCOVA revealed that parental involvement extensively impacts motivation (F(1, 298) = 12.45, p < 0.001), with socioeconomic fame also contributing to variance in motivation effects. These findings underscore the essential function of parental engagement in fostering student motivation and highlight implications for instructional coverage and exercise.